Research on Petrophysical Properties of Chosen Samples from the Point of View of Possible CO2 Sequestration - Klempa, Martin; Porzer, Michal; Bujok, Petr; Pavluš, Ján (GeoScience Engineering, 2013)
Man-made CO2 emissions (the so called anthropogenic CO2 emissions) and their increasing trend can be, by some scientists, considered a serious menace for the sustainable development of mankind, and their reduction a prerequisite for the environment protection. Carbon dioxide is one of the most important gases that cause a greenhouse effect which warms up the earth surface as a consequence of a different heat flow between the earth and the atmosphere. Our laboratory measurements determined the porosity, permeability and grain density for clastic sedimentary rock samples which were drilled from an underground gas storage facility. Additionally, our results showed a reduction in porosity and permeability after a confining pressure was applied. We assume that this effect is caused by internal structure changes due to the repeatedly increased and decreased net pressure applied to the samples.